Modelling mobile advertising, consumer response and mobile shopping behavior. A post COVID-19 pandemic perspective - Forbes Makudza; Rosemary Farayi Masaire; Tendai Makwara; Lucky Sibanda; Tafadzwa Hatidani Tafataona Machaka (Cogent Business & Management, 2024)
This study investigated the impact of five mobile advertising strategies on consumer attention and interest to bolster mobile shopping. The study aimed to promote and enhance mobile shopping acceptance and usage. The stimulus-response of consumer attention and interest was modelled to directly impact the intention to use mobile shopping, whilst mobile shopping intention predicts actual mobile shopping. The AIDA model of consumer decision-making and the technology adoption model informed the study. Data for the study were collected from participants in Harare, Zimbabwe, using a structured questionnaire. The study validated 211 responses, which were analysed using a structural equation modelling technique (SEM). The study confirmed the importance of mobile shopping for consumer engagement and recommended enhancing mobile advertising to boost attention and interest, thereby increasing mobile shopping.
Keywords: 650; Consumer attention; consumer interest; mobile advertising; mobile commerce; mobile shopping